Comorbidities of Patients With Idiopathic Pulmonary Fibrosis in Four Latin American Countries. Are There Differences by Country and Altitude? - Gonzalez-Garcia, Mauricio; Rincon-Alvarez, Emily; Alberti, Maria Laura; Duran, Mauricio; Caro, Fabian; Venero, Maria del Carmen; Liberato, Yuri Edison; Buendia-Roldan, Ivette (Frontiers in Medicine, 2021)
Background: Comorbidities in idiopathic pulmonary fibrosis (IPF) affect quality of life, symptoms, disease progression and survival. It is unknown what are the comorbidities in patients with IPF in Latin America (LA) and if there are differences between countries. Our objective was to compare IPF comorbidities in four countries and analyze possible differences by altitude. Methods: Patients with IPF according 2012 ATS/ERS/JRS/ALAT guidelines, from two cities with an altitude of ≥2250m: Mexico City (Mexico) and Bogotá (Colombia) and from three at sea level: Buenos Aires (Argentina) and Lima and Trujillo (Peru). Comorbidities and pulmonary function tests were taken from clinical records. Possible pulmonary hypertension (PH) was defined by findings in the transthoracic echocardiogram of systolic pulmonary arterial pressure (sPAP) >36 mmHg or indirect signs of PH in the absence of other causes of PH. Emphysema as the concomitant finding of IPF criteria on chest tomography plus emphysema in the upper lobes. ANOVA or Kruskal Wallis and χ2 tests were used for comparison. Results: 276 patients were included, 50 from Argentina, 86 from Colombia, 91 from Mexico and 49 from Peru. There prevalence of PH was higher in Colombia and Mexico (p<0.001), systemic arterial hypertension in Argentina (p<0.015), gastro-esophageal reflux and dyslipidemia in Colombia and Argentina (p<0.001) and diabetes mellitus in Mexico (p<0.007). Other comorbidities were obesity (28.4%), coronary artery disease (15.2%) and emphysema (14.9%), with no differences between countries. There was more PH in the altitude cities than those at sea level (51.7 Vs 15.3%, p<0.001). In patients from Bogotá and Mexico City, arterial oxygen pressure, saturation (p<0.001) and carbon monoxide diffusing capacity (p=0.004) were significantly lower than in cities at sea level. Conclusions: In this study with a significant number of patients, we were able to describe and compare the comorbidities of IPF in four LA countries, which contributes to the epidemiological data of this disease in the region. The main results were the differences in comorbidities between the countries and more PH in the subjects residing in the cities of higher altitude, a finding that should be validated in future studies.